Conformidade de memória : a influência de respostas externas no reconhecimento de faces humanas - Weslley Santos Sousa (2019)
Memory conformity occurs when individuals adjust their memory decisions to the context in which they are inserted. Results obtained in studies with this phenomenon have been relevant in eyewitness situations. In two experiments, we investigated how external responses influence cognitive processes of memory recognition. One hundred participants (50 in each experiment) underwent a human face recognition task and the confidence levels of the responses were recorded on a 3-point scale. These participants were led to believe that during the test they would have access to answers from another participant who allegedly had previously taken the test. Participants were correctly informed of the validity of external responses (about 75%), however these responses were automatically generated by the software used. In the first experiment, participants studied 194 faces for 2 seconds each. In the second, the same material was used, however, each face was studied twice, for 3 seconds each time. In both experiments, participants were influenced by external responses even when reporting high confidence on their responses. Confidence, in turn, was only affected by the validity of external responses on correct rejections and not during hits.